Impact of Spinal Cord Stimulation on Opioid Dose Reduction: A Nationwide Analysis. (18th December 2021) - Adil, Syed M; Charalambous, Lefko T; Spears, Charis A; Kiyani, Musa; Hodges, Sarah E; Yang, Zidanyue; Lee, Hui-Jie; Rahimpour, Shervin; Parente, Beth; Greene, Kathryn A; McClellan, Mark; Lad, Shivanand P
Graphical Abstract: